Morphology of silence in The Last Gift by Abdulrazak Gurnah (ENTHYMEMA, 2021)
In contemporary narrations of migration and diaspora, the intersection of memory and storytelling unveils the traumas of dislocation and retrieves personal and collective pasts. In The Last Gift (2011) by Abdulrazak Gurnah the recollection takes places through a narrative structure privileging the unspoken, and giving silence, articulated in various forms, from aphasia to mutism, as well as amnesia, a central role. The gradual unfolding of Abbas’s story is evoked by the writer through an omniscent narrator and a multiple focalization, depicting the microcosm of a family hiding secrets only partially revealed. The novel interweaves fragments of stories, set in different times and spaces, which converge in a tape recording – the last gift by a father born in Zanzibar to his English children. The issue of identity is questioned in a tale of great emotional impact. The readers are provided with a number of possible interpretations.
Keywords: Diaspora; Abdulrazak Gurnah; memory; silence; The Last Gift